An urban fern refugium: Municipal Ecological Reserve of Avellaneda (Eco Área) (Buenos Aires, Argentina) - Yañez, Agustina (2021)
The riparian forest is one of the most diverse environments of the La Plata River plains. It is represented by patches of humid forests, which are a valuable source of ecosystem services and have recreational and educational potential. However, the riparian forest has undergone constant modification, worsened by private real-estate developments and a lack of government regulation. Among the reserves that protect the riparian forest, the Municipal Ecological Reserve of Avellaneda is the closest to the southern limit of the Autonomous City of Buenos Aires. Although there are around 300 species of wild fauna and flora informally registered in the area, there are only a few studies published about its biodiversity. In this work, the diversity of thirteen native and exotic ferns in the core area (Eco Área) of the reserve is characterized, the origin of the species is also evaluated and comparisons are made with other nearby protected areas. The Eco Área of the Reserve plays an important role as part of the urban reserve corridor of the La Plata River plains and constitutes a refuge for both native and exotic ruderal species. The present work represents the basis for future studies about the population dynamics and the colonization strategies of the ferns.